1991
DOI: 10.1007/bf00317584
|View full text |Cite
|
Sign up to set email alerts
|

Stable oxygen and hydrogen isotope composition of leaf water in C3 and C4 plant species under field conditions

Abstract: In this paper we make comparisons between the observed oxygen and hydrogen stable isotope composition of leaf water and the predictions of the Craig-Gordon model of evaporative isotopic enrichment. Comparisons were made among two C species (Chenopodium album and Helianthus annuus) and two C species (Amaranthus retroflexus and Kochia scoparia), when plants were exposed to natural environmental conditions in the field. There were significant differences among the species for the hydrogen and oxygen isotopic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 26 publications
3
41
0
2
Order By: Relevance
“…5 and 6). Some previous studies have found that the Craig-Gordon model predicted a higher degree of heavy isotopic enrichment than observed in bulk leaf water measurements Leaney et al, 1985;Flanagan and Ehleringer, 1991;Flanagan et al, 1991a;Wang and Yakir, 1995). Although the results of this study also showed a similar trend between modeled and measured bulk leaf water values, the generality of the model is still clearly evident over the range of leaf waters that far exceeds natural conditions (Figs.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…5 and 6). Some previous studies have found that the Craig-Gordon model predicted a higher degree of heavy isotopic enrichment than observed in bulk leaf water measurements Leaney et al, 1985;Flanagan and Ehleringer, 1991;Flanagan et al, 1991a;Wang and Yakir, 1995). Although the results of this study also showed a similar trend between modeled and measured bulk leaf water values, the generality of the model is still clearly evident over the range of leaf waters that far exceeds natural conditions (Figs.…”
Section: Discussionsupporting
confidence: 68%
“…Flanagan et al (1991b) modified the Craig-Gordon model to include the effects of a turbulent boundary layer on the kinetic fractionation factors that were appropriate for molecular diffusion only. In some cases the CraigGordon model predicts a greater isotopic enrichment than was actually observed in bulk leaf water Leaney et al, 1985;Flanagan and Ehleringer, 1991;Flanagan et al, 1991a;Wang and Yakir, 1995). Since the value of leaf water at the site of carbohydrate metabolism is an essential component of models predicting the hydrogen and oxygen isotopic composition of plant organic matter, carefully controlled experiments are needed to determine how sound these leaf water models are under different environmental conditions.…”
mentioning
confidence: 99%
“…Although the Craig-Gordon model basically describes water enrichment at the sites of evaporation compared with locally transpired water, it cannot adequately account for other aspects of leaf water enrichment, particularly the spatial variation of leaf water 18 O and/or D contents (Luo and Sternberg, 1992; Bariac et al, 1994;Wang and Yakir, 1995;Helliker and Ehleringer, 2000). Also, the Craig-Gordon model has often been found to overestimate the isotopic enrichment of bulk leaf water (Allison et al, 1985; Bariac et al, 1989;Walker et al, 1989;Walker and Brunel, 1990;Yakir et al, 1990;Flanagan et al, 1991aFlanagan et al, , 1991bFlanagan et al, , 1994Wang et al, 1998). To explain such observations, several other models have been suggested in conjunction with the Craig-Gordon model, namely the two-pool model (Leaney et al, 1985), the Péclet model , and the string-of-lakes model (Gat and Bowser, 1991).…”
mentioning
confidence: 99%
“…Il ∆ L misurato è stato così ricalcolato attraverso il metodo del bilancio di massa (Roden & Ehleringer 1999, Cernusak et al 2003, utilizzando un fattore di correzione (12.9% ± 0.46, media ± errore standard, n = 16), ottenuto separando il contributo dell'acqua nelle nervature rispetto a quello totale fogliare. Alcuni autori hanno stimato che la frazione di volume incluso nelle nervature fogliari può variare dal 10 al 30% del totale (Leaney et al 1985, Flanagan et al 1991b). I valori massimi sono ottenuti in specie con presenza di una fitta rete di nervature primarie e secondarie.…”
unclassified
“…L'assunzione dell'equilibrio è spesso violata, poiché nei sistemi naturali si assiste spesso a variazioni dei parametri ambientali (Hardwood et al 1998). Pertanto, fondamentale ai fini dell'utilizzazione di questi modelli è la stima del tempo necessario per raggiungere l'equilibrio, che studi passati stimano in 1-5 ore (Flanagan et al 1991b, Yakir et al 1993; in genere, le condizioni di equilibrio vengono raggiunte più rapidamente nel caso di foglie a lamina sottile e in situazioni dove non si hanno forti variazioni dei parametri ambientali. Ad ogni modo, nel nostro caso la correzione ha permesso al modello Péclet di ottenere una stima molto buona del ∆ L misurato e una riduzione della discrepanza con il modello Craig e Gordon.…”
unclassified